Biodegradable active food packaging structures based on hybrid cross-linked electrospun polyvinyl alcohol fibers containing essential oils and their application in the preservation of chicken breast fillets. (March 2021) - Göksen, Gülden; Fabra, Maria José; Pérez-Cataluña, A.; Ekiz, H. Ibrahim; Sanchez, Gloria; López-Rubio, Amparo
Highlights: Essential oils-containing PVOH electrospun fibers were developed as active coatings. Citric acid was used as crosslinker to keep the integrity of the active fibers. The coatings with good water and thermal stability were applied to chicken fillets. The coatings inhibited lipid oxidation and microbial growth improving meat colour. Abstract: Active food packaging materials produced through electrospinning of polyvinyl alcohol (PVOH) containing essential oils (EOs) from two broadly used spices ( Laurus nobilis –LEO- and Rosmarinus officinalis -REO-) were developed and applied to chicken breast fillets with the aim of prolonging their shelf-life. Citric acid (CA) was successfully incorporated as a natural cross-linker and the developed electrospun structures were heat-treated to promote both the crosslinking and the crystallization of the PVOH matrix. Initially, the morphology, water solubility, physicochemical and thermal properties of the developed structures were evaluated. Then, the antioxidant and antibacterial efficiency of PVOH-EOs hybrid structures were evaluated when directly applied onto an inoculated side of chicken breast fillets. These annealed active food packaging structures containing EO and CA exhibited improved water resistant and thermal stability with respect to their non-crosslinked counterparts. Although part of the EOs content was degraded after the annealing process, the remaining amount in the PVOH samples inhibited the lipid oxidation process up to 68 % and displayed enhanced antimicrobial effectiveness when applied onto chicken breast fillets, having a beneficial effect on both the pH and color parameters during storage.